Nondoped, deep-blue, organic light-emitting diodes with low-efficiency roll-off based on a simple anthracene–triazole hybrid fluorescent molecule. (November 2021) - Cang, Miao; Cui, Wei; Zhou, Huayi; Wang, Runze; Sun, Mizhen; Ying, Shian; Sun, Qikun; Pan, Yuyu; Xue, Shanfeng; Yang, Wenjun
Abstract: Anthracene is a traditional blue-fluorescence group with excellent electron-transporting ability and high fluorescence quantum efficiency. With the increasingly wide application of anthracene derivatives in electroluminescence (EL) fields, how the molecule is constructed becomes particularly critical owing to the natural flat conformation of the anthracene group, which quenches fluorescence in the aggregated state. In this study, we designed and synthesized a simple donor–acceptor-type molecule by hybridizing anthracene with triazole [3-(4-(anthracen-9-yl)phenyl)-4, 5-diphenyl-4 H -1, 2, 4-triazole (ANTZ)]. In this molecule, anthracene acts as an electron donor, and the triazole unit with a twisting spatial construction and electron-withdrawing ability can not only inhibit the flat-stacking effect between anthracene and anthracene but also demonstrate carrier-transport ability to mimic anthracene. The optimized nondoped, deep-blue Device I using ANTZ as an emitter exhibits deep-blue-fluorescence emission with smaller Commission Internationale de I'Eclairage (CIEy) coordinates of 0.13, a maximum external quantum efficiency (EQE) of 3.3%, and a low-efficiency roll-off of 3.0%, which was a significant improvement relative to Device II using a traditional 2-methyl-9, 10-bis(naphthalen-2-yl)anthracene emitter. The superior EL properties of Device I suggest its effectiveness as a molecular design for deep-blue emitters based on anthracene derivatives. Graphical abstract: Image 1 Highlights: A novel molecule was designed by hybridizing anthracene with triazole. Non-doped ANTZ-based device exhibits a negligible efficiency roll-off of 3 %. Deep-blue ANTZ-based device shows a small CIEy value. This method is promising in the exploration of deep-blue OLED fields.